Analysis of Mechanical Property of Combined Output Plate of Real-time Non-clearance Precision Ball Transmission based on Size Error - Jiang Wei; An Zijun; Zhang Yue; Qin Kai (Jixie chuandong)
In view of the innovative construction of combined output plate of real-time non-clearance precision ball transmission,the mechanical model of engagement pair contact point is established based on size error of balls and guide groove. The actual contact angle and normal force are deduced by using the torque balance equation and the contact point stiffness coefficient,and result is exact calculated. The normal force is converted to a distributed force on contact zone. The deformation,pressure and dimensionless stress of contact center zone are analyzed and the law of change that effected by error is analyzed. The results show that the mechanical properties of combined output plate are impacted by the two kinds of errors. The distribution of normal force has an obvious change as the varying of the ball size errors,and it is the main factor for mechanical properties of combined output plate. The research result provides theoretical basis for the design and analysis of combined output plate of precision ball transmission.